Do regulatory policies on auditing affect executive pay?. (1st January 2013) - Chen, Hui; Jeter, Debra; Yang, Ya-Wen
The purpose of this paper is to investigate the impact on pay-performance sensitivity of a commitment by regulatory bodies to monitor the auditing of managers' financial reporting. Executive incentive pay is often analysed in isolation of the regulatory environment of auditing and financial reporting; this omission implies an assumption of no significant relation between the two. In this paper, we show that the effects of an imposed mandatory audit of the auditor could reach the incentive pay of executives in the firms being audited. We construct a model to depict two distinct regulatory environments: a pre-commitment economy in which the regulator checks auditors on a random basis; and a post-commitment economy in which the regulator commits to the inspection of auditors' work. The model predicts that a more rigorous audit environment leads to more reliable auditing and reporting, and to an increase in pay-performance sensitivity for executives. Consequently, the corresponding managerial effort under higher pay-performance sensitivity will also increase. The study provides insight into some positive aspect of the changes resulting from the passage of Sarbanes-Oxley.